Pressure from Parent Entity Owners and Non-Controlling Interests Stimulates Management to Income Smoothing: Evidence from Asia - Kusuma, Marhaendra Kusuma; Fazlinda Binti Ab Halim; Fahad Hari Putra Maulana; Sanju Kumar Singh; Mariano Nunes (Riset Akuntansi dan Keuangan Indonesia, 2026)
This study examines effect of pressure from parent entity owners (PEO) and non-controlling interest (NCI) on income smoothing and the moderating role of independent commissioners. Observational data from 2,740 firm-years of publicly traded companies in 12 Asian countries during 2021–2025 are used. The results support agency theory and fraud triangle theory, indicating that pressure from PEOs and NCIs significantly drives income smoothing practices, while the effectiveness of independent commissioners can mitigate the influence of both pressures. This study offers an original contribution by disaggregating shareholder pressure by ownership type (PEOs and NCIs) and the moderating role of independent oversight.